Development of Interactive Teaching Materials Supplements to Improve Learning Results in the Digestive System - Susanti, Alfiyana; Ridlo, Saiful; Widyaningrum, Priyantini (Journal of Innovative Science Education)
Interactive teaching materials supplement in the form of additional teaching materials containing materials and assignments that are linked online and given to students so that they can learn independently. This study aims to test the validity and effectiveness of these supplements in improving learning outcomes of the digestive system material. The research method uses research and development (R & D) which consists of research, development, validation, and testing. Analysis of development needs is carried out on learning constraints, teaching materials, and digestive system materials. Teaching materials are developed from the results of the analysis and then validated and tested for legibility. The trial was carried out at SMA N 1 Brebes with a one-group pretest-postest research design, which was carried out in one group only without a comparison group. The results of the validation by media experts showed an index of 87.31% and material experts showed an index of 85.41% with valid criteria, the module readability test resulted in an index of 87.48% with criteria easy to understand. The results of the application of learning using this supplement showed an effect on improving student learning outcomes with an average N-gain test of 0.57 which was included in the moderate criteria.